Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Dalam Membayar Pajak Bumi Dan Bangunan Di Kecamatan Boja Kabupaten Kendal - Ipung Firmansyah Firmansyah; Maryono (Universitas Sains dan Teknologi Komputer, 2022)
This study aims to analyze the effect of tax sanctions, tax knowledge, and taxpayer awareness on taxpayer compliance. The population of this research is land and building taxpayers in Boja District, Kendal Regency with a sample of 100 taxpayers. The calculation of the sampling was calculated by random sampling using the formula Slovin and got the results as 100 respondents. Primary data using a questionnaire distributed to taxpayers This study has theoretical and implications practical. This study uses Multiple Linear Regression Analysis The results showed: 1). Tax sanctions have no significant negative effect on taxpayer compliance. 2). Tax knowledge has a positive and significant effect on taxpayer compliance. 3). Taxpayer awareness has a positive and significant effect on taxpayer compliance.